Trust as the Sport Team Cohesion Factor (Journal of Universal Excellence, 2026)
Research Question (RQ):  What role do the trust in teammates and trust in coach have and how strong do they influence the cohesiveness of a sport team?Purpose: The aim is to contribute to the theory of human resource management by explaining the relationships between the perception of the HRM quality, trust in co-workers and superiors, and team cohesiveness in the context of sport team. The main goal is to develop a model based on theory and test its validity in practice.Method: The model was tested on data collected from 559 athletes from 73 basketball clubs by structural equation modelling and Sobel's test of mediation.Results: Athletes’ trust in the coach and in the teammates has direct positive effect on the team cohesiveness. The perception of the HRM quality has a strong direct positive effect on trust in the coach, but does not directly affect cohesiveness or trust in teammates. Nevertheless, the positive effect of the HRM perception indirectly spills over through the athletes’ trust in coach on their trust in teammates, and indirectly also increases the team cohesiveness.Organization: The article provides a new scale for measuring the perception of HRM quality. It reminds coaches of the importance of athletes’ trust in coach, as it stimulates trust among athletes and cohesiveness.Society: The study emphasizes the importance of interpersonal relationships and explains how people turn their trust into a sense of better connection with co-workers.Originality: A new scale for measuring the perception of the HRM quality. It is the first study of relationships between the quality of HRM, two trust relations and team cohesiveness within sport team.Limitations / further research: Use of subjective data and their collection in only one time point. We recommend further research between sports clubs over a longer period of time, in different environments and in different sports.
Keywords: basketball; coach; cohesiveness; HRM; team; trust